Coproduction of clean syngas and iron from woody biomass and natural goethite ore - Kudo, S.; Sugiyama, K.; Norinaga, K.; Li, Chun-Zhu; Akiyama, T.; Hayashi, J. (Elsevier Science Ltd, 2013)
Conversion of biomass into clean syngas was studied considering application of low-grade iron ore toreforming of tar. Chipped cedar with moisture content of 0.1–10.1 wt% was continuously pyrolysed at550 C, and the nascent volatiles were subjected to reforming at 690–800 C in a bed of mesoporoushematite derived from a type of natural goethite. The yield of heavy tar (b.p. > 350 C) decreased from18.8 to less than 0.01 wt% during the reforming mainly by its oxidation by the ore and conversion intocoke. The hematite was reduced completely to magnetite and further but incompletely to wustite. Theformation of iron was inhibited by high CO2/CO and H2O/H2 ratios of the gas phase. The coke-loaded magnetite/wustite mixture was, however, an excellent precursor of iron. Reheating the spent ore up to 800 C in the absence of the volatiles reduced the magnetite/wustite to wustite/iron obeying direct and indirect reduction mechanisms. Repeated cycles of such reheating and reforming converted the volatiles and ore into syngas with a total tar concentration as low as 10 mg Nm3-dry and coke-loaded iron, respectively. Contribution of the steam reforming with iron–wustite redox cycles became more important as the reforming-reheating cycles were repeated.